An Analysis of Teaching Strategies Used by English Teacher to handle student with Attention Deficit Hyperactivity Disorder (ADHD) in A2 class at Aura Sukma Insani Bilingual Kindergarten - ., Ni Luh Ratih Cris Andini; ., Prof. Dr. Ni Nyoman Padmadewi, M.A.; ., I Nyoman Pasek Hadi Saputra, S.Pd., M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
This study aimed to describe teaching strategies to handle ADHD student in A2 class at Aura Sukma Insani Bilingual Kindergarten, SINGARAJA and the reasons of English teacher used some strategies to handle ADHD student in the learning process .This study also told about the teacher’s problems in handling ADHD student and the achievement that got from ADHD student in the learning process. This study used descriptive research design by involving ADHD student in A2 class. The objects of this study were the teaching strategies that used by English teacher to handle ADHD student in the learning process. The data were collected by conducting interviews, took some picture and document analysis. Based on the result of the data analysis, the researcher found that the English teacher used some kinds of teaching strategies in the learning process such us: Total Physical Response and modeling, Repetition drill, Verbal and Non verbal, Co-operative learning (group discussion) and games. The teacher told some reasons in used of those kinds of teaching strategy in the learning process, to make ADHD student always focus and enthusiasm in the learning process. In implemented those kinds of teaching strategies the teacher found some problems in handling student with ADHD in the class and, the teacher also saw ADHD student got some achievements in following the learning process. keyword : Teaching Strategies and ADHD student